Strategic Environmental Assessment of the Territory as a Public Management Instruments for Technological Development. A Case of Ukraine - Mykolaichuk Mykola (Sciendo, 2021)
The study aims to substantiate theoretical and methodological aspects of the use of strategic environmental assessment as an instrument for public regulation of the ecological status of territories. The research methodology is based on using a systematic approach for conducting a strategic environmental assessment of the possibility of environmental problems and threats posed by the implementation of long-term projects and current activities. The development of ecological balance, comparison of the results of normative and exploratory forecasts of the state of the environment become the basis for the formation of goals of strategic environmental management, the appearance of a set of measures for the conservation and restoration of natural resources. Identification of factors influencing the state of the environment is a necessary condition for the prevention of pollution of territories, inefficient use of natural resources, justification of the essential measures of state regulation to ensure the achievement of goals. The practical experience of assessing the achievements in the management of the conditions of the environment is illustrated by the example of regions of Ukraine. The proposed approach to the development of the ecological balance and the methodology of complex assessment of the ecological status of the territory have scientific novelty and contribute to the assessment of the effectiveness of public administration balanced development of the territories.